Erectile Dysfunction After External Beam Radiotherapy for Prostate Cancer - Pinkawa, Michael; Gagel, Bernd; Piroth, Marc D.; Fischedick, Karin; Asadpour, Branka; Kehl, Mareike; Klotz, Jens; Eble, Michael J. (European urology, 2009)
There is a lack of prospective studies focusing on the sexual quality of life of prostate cancer patients after conformal radiotherapy (RT). To evaluate the incidence, progression, and predictive factors for erectile dysfunction (ED). Patients who responded to the sexual domain of the Expanded Prostate Cancer Index Composite (EPIC) questionnaire before and more than 1 yr after RT and never received an antiandrogen treatment were included (n=123). RT dose was 70.2–72Gy. Eleven patients used a phosphodiesterase-5 (PDE-5) inhibitor. Patients responded to the EPIC questionnaire before (time A), at the last day (B), a median time of 2 mo after (C), and 16 mo after (D) RT. In a multivariate analysis, risk factors (patient age, prostate volume, planning target volume, use of PDE-5 inhibitor, comorbidities) were tested for their independent effects on ED before and after RT. Sexual function and bother scores had already decreased by the end of RT (median function and bother scores at times A/B/C/D: 41/30/32/24 and 75/50/50/50). Initial function scores correlated well with late function scores (r=0.7; p<0.001). The ability to have an erection was reported by 81%/72%/74%/60% (preserved erectile ability in 70% at time D), erections firm enough for sexual intercourse by 44%/33%/35%/27% (preserved erections sufficient for intercourse in 53% at time D) of patients. A higher patient age and diabetes were predictive of both a pre-existing ED and a post-RT acquired ED. Nightly erections before treatment proved prognostically favourable (at least weekly vs. < weekly—hazard ratio of 5.9 for preserved erections sufficient for intercourse; p=0.01). Higher rates of ED can be expected with longer follow-up. The incidence of ED progressively increases after RT. Patient age and diabetes are risk factors for both pre-treatment and RT-associated ED. Nightly erections before RT proved prognostically favourable. The incidence of erectile dysfunction progressively increases after external beam radiotherapy. Patient age and diabetes are risk factors for both pre-treatment and radiotherapy-associated erectile dysfunction. Nightly erections before treatment proved prognostically favourable.